MOF-Based Materials with Sensing Potential: Pyrrolidine-Fused Chlorin at UiO-66(Hf) for Enhanced NO2 Detection - Queirós, Carla (2022)
An efficient strategy to develop porous materials with potential for NO2 sensing was based in the preparation of a metal-organic framework (MOF), UiO-66(Hf), modified with a very small amount of meso-tetrakis(4-carboxyphenyl) N-methylpyrrolidine-fused chlorin (TCPC), TCPC@MOF. Chlorin’s incorporation into the UiO-66(Hf) framework was verified by several characterization methods and revealed that the as-synthesized TCPC@MOF brings together the chemical stability of UiO-66(Hf) and the photophysical properties of the pyrrolidine-fused chlorin which is about five times more emissive than the porphyrin counterpart. TCPC@MOF was further incorporated into polydimethylsiloxane (PDMS) and the resulting TCPC@MOF@PDMS film was tested in NO2 gas sensing. It showed notable sensitivity as well as a fast response in the range between 0.5 and 500 ppm where an emission intensity quenching is observed up to 96% for 500 ppm. This is a rare example of a chlorin-derivative used for gas-sensing applications through emission changes, and an unusual case of this type of optical-sensing composites of NO2.